Gugurnya Kebijakan Sekolah Bertaraf Internasional: Investasi Pendidikan VS Komersialisasi Pendidikan - Edison Edison (Magister Administrasi Publik, 2012)
This paper discusses about education policy with a focus on international school (RSBI). This is one of innovation in education policy aimed at improving the quality of education in Order to accelerate internationally competitive. In Permendagri 78/ 2009 on the Implementation of the International School of Elementary and Secondary Education level, SBI/RSBI have been constructed with a set of standards in the implementation of international education. The standard has a target to achieve hat quality education. However, since 2003, Law 20/2003 on National Education System has become a public discourse polemic. In fact, the embodiment of the spirit of